2018
DOI: 10.2147/cmar.s186236
|View full text |Cite
|
Sign up to set email alerts
|

IRF1 inhibits the proliferation and metastasis of colorectal cancer by suppressing the Ras-Rac1 pathway

Abstract: BackgroundInterferon regulatory factor 1 (IRF1) plays a role in the immune response, cellular necrosis, DNA damage, and DNA repair, offering an attractive target for anticancer treatment. However, little is known about the role of IRF1 in the regulation of CRC progression.MethodsQuantitative reverse transcription-PCR, Western blot, and immunohistochemistry were used to examine the expression level of IRF1; Cell Counting Kit-8, migration assay, and xenograft mouse models were used to examine the function of IRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…IRF1, which belongs to the IRF family (34), is weakly expressed in resting dendritic cells and macrophages, but is induced by interferon-γ (IFN-γ) in M1 polarized macrophages (35,36). Previous studies have revealed that IRF1 inhibited the proliferation and metastasis of CRC (37,38). UBE2L6, which is also known as UBCH8, promotes apoptosis in cervical cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…IRF1, which belongs to the IRF family (34), is weakly expressed in resting dendritic cells and macrophages, but is induced by interferon-γ (IFN-γ) in M1 polarized macrophages (35,36). Previous studies have revealed that IRF1 inhibited the proliferation and metastasis of CRC (37,38). UBE2L6, which is also known as UBCH8, promotes apoptosis in cervical cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of in vivo experiments, it was shown that thiopurines treatments (TG) inhibited CAC in the AOM/DSS mouse model, via decreased β-catenin in a RAC1-dependent mechanism [ 144 ]. In the context of epithelial cell targeting, EMT and metastatic potential might be inhibited upon activation of RAC1; for instance, upon CSRP2 treatment (Hippo-ERK-PAK/LIMK/cortactin) [ 145 ], miR-142-3p transfection [ 146 ], upregulation of SSH3 (LIMK) [ 147 ] or PLS1 (ERK1/2) [ 148 ], downregulation of DMTN [ 149 ], or IRF1 suppression [ 150 ]. Recent work from An et al revealed the different behavior of RAC1 inhibition in combination with irradiation on cell cycle.…”
Section: Rac1 (Ras-related C3 Botulinum Toxin Substrate 1)mentioning
confidence: 99%
“…Cancer is a complex group of diseases characterized by uncontrolled cell growth. Excess of Rac1 activity has been linked to several cancer types such as breast cancer, colorectal cancer, gastric cancer, prostate cancer, and cervical cancer [60,61,62,63,64,65]. In particular, Rac1 is involved in several phases of cancer development, as it can promote cancer initiation, cancer progression, and metastases through its role in gene transcription, cell cycle progression, neovascularization, cell adhesion, migration, and invasion [56,66,67,68,69].…”
Section: Rac1 In Cancer: Role Of Rac1 and Rabs In Cell Migration Amentioning
confidence: 99%